2020
DOI: 10.1024/0301-1526/a000878
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation treatment of cancer patients with deep or superficial leg vein thrombosis – a retrospective observational study of German statutory health insurance claims data (the CERTIFICAT initiative)

Abstract: Summary: Background: Thrombosis is a common complication of cancer with a negative impact on quality of life and overall prognosis. Guidelines recommend low-molecular-weight heparin (LMWH) as initial and prolonged anticoagulation treatment. Little is known about current treatment patterns of these patients in ambulatory care. Patients and methods: The current retrospective observational study interrogates a large German statutory health insurance claims database in order to understand which kind of data can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The results of GeCAT differ in some important aspects from those obtained in CERTIFICAT, a retrospective analysis of insurance claims data collected in Germany from 2012 to 2015 [10]. Based on this analysis, more than 80% of prescriptions for CAT patients in the outpatient setting were made by general practitioners and less than 10% by hemato-oncologists.…”
Section: Discussionmentioning
confidence: 88%
“…The results of GeCAT differ in some important aspects from those obtained in CERTIFICAT, a retrospective analysis of insurance claims data collected in Germany from 2012 to 2015 [10]. Based on this analysis, more than 80% of prescriptions for CAT patients in the outpatient setting were made by general practitioners and less than 10% by hemato-oncologists.…”
Section: Discussionmentioning
confidence: 88%
“…Around 90.0% of incident thromboseswere diagnosed in the outpatient sector. The study population of 7,313 cancer patients with incident thrombosis and at least one outpatient prescription of an anticoagulant was identified using the defined criteria 17 between 2012 and 2015 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The bleeding prevalence during and after anticoagulation prescription was analyzed for gastrointestinal bleedings combined with inpatient stays. Further details regarding study design can be found in the publication from Schellong et al 17…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations